GAMBARAN PAPIL NERVUS OPTIKUS PADA NEUROPATI OPTIK TOKSIK METANOL SEBELUM DAN SESUDAH TERAPI DENGAN METIL PREDNISOLON - , NINDAYU RIZKI PUJIASTUTI, dr. Hartono, Sp.M(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Purpose : To determine the optic disc of the eye in patients with toxic optic neuropathy due to alcohol consumption by administration of methyl prednisolone Method :Descriptive non-experimental through retrospective review . Results :There were 18 patients came to the department of ophthalmology RSUP Dr.Sardjito during five years between January 2008 to April 2013. In the cases here, 32 eyes or 88.89 % margin optic disc of optic nerve were firm and 4 eyes or 11.11 % margin optic disc of optic nerve were no expressly. After control I,the optic disc of optic nerve obtained after treatment with the use of methyl prednisonol 17 eyes or 94.44 % with margin optic disc of optic nerve were firm, 1 eye or 5.56 % with margin optic disc of optic nerve were no expressly and 18 eyes or 50 % did not come back to hospital.After control II, 8 patients or 16 eyes with margin papil optic nerve were firm . 18 people or 36 eyes of toxic optic neuropathy diagnosed obtained color of the optic disc optic nerve before treated with methyl prednisonol the 32 eyes or 88.89 % with a pale optic disc optic nerve , 1 eye or 2.78 % with optic disc of optic nerve colored were hyperemia and 3 eyes or 8.33% with optic disc colored were slightly hyperemic optic nerve. Control I after treated with methyl prednisonol using the 18 eyes or 50 % with a pale optic disc optic nerve , 18 eyes or 50 % patients did not come back to the hospital . 11 eyes or 68.75 % with pale optic disc optic nerve , 5 eyes or 31.25 % with optic disc optic nerve hyperemia and 20 eyes or 55.6 % of patients did not come back to the hospital for control II . Conclusions : The proportion of patients with optic neuropathy toxic methanol was dominated by men as much as 100 % and productive age.Patients with toxic optic neuropathy methanol between 19 to 60 years old.Atrophy papilledema seen the most rapidly in the first week and delayed after 2 months.All patients with toxic optic neuropathy after treatment with methyl prednisolone optic disc boundary into firm.After control II more than half of the optic disc becomes pale or shows atrophy of the optic disc. Keyword: toxic optic neuropathy , optic dic, methanol,methyl prednisolone.